Incorporation of ionic rare earth elements as a form of microbial environmental remediation - Rassy, Wadih Y.; Ripper, Doris; Pomare, Eliana; Winkler, Sebastian; Koppensteiner, Anita; Spadiut, Oliver; Schild, Dominik (Frontiers in Environmental Science, 2023)
Modern society is heavily dependent on critical raw materials, such as rare earth elements, for use in electronic devices. The increasing demand for these materials has led to the need for environmentally friendly methods of processing non-recycled materials from e-waste and wastewater, as well as waste streams from cleaning and manufacturing facilities. Modern society's dependence on such materials is growing by the day, and with it, the need for environmentally friendly processing of non-recycled materials from e-waste and wastewater in the form of "end-of-life" products, as well as waste streams from cleaning and manufacturing facilities. As these are problematic indications for modern isolation methods in industry, these sources may be more suitable for new techniques as they have low concentration and high throughput for bioaccumulation. Chemical methods using nanomaterials are already being tested for their possibilities but still depend on acids and harsh chemicals. Microorganisms on the other hand can adsorb/absorb REEs in a more ecological way. Previous studies could already show that it is possible to accumulate REEs in the precipitates of bacterial cultures spiked with REEs to a value of over 50%. However, the question arose whether the rare earths were spun into the pellets by centrifugation, adsorbed or really incorporated in the cells. Therefore, we established a new easy-to use experimental design in which the microorganisms were spiked with an REEs standard and washed, to minimise falsification of measurements by peripheral binding of ions before being analysed for REE content using an ICP-OES. The bioaccumulation of rare earths in microorganisms was monitored yielding an uptake rate of up to 53,12% of overall present ionic REE concentration. In this manuscript we present the different concentration measurements that were taken during the process, before and after washing of the cells, to create a full picture of the localisation, binding, incorporation and occurrence of the ions of interest. The setup also showed a correlation between the introduction method of rare earths and the uptake of certain elements, that might be correlated to the differentiation between light and heavy rare earth elements, while Y and Sc often seem to represent outliers.